From observation to practice: the importance of experience for nursing and pharmacy academics in an oncological clinic (Research, Society and Development, 2022)
Cancer is termed as a group of diseases in which uncontrolled cell expansion occurs. The treatment modalities are surgery, radiotherapy and chemotherapy. From this, experience through internships is essential for the development of skills and abilities for students in the health area. Therefore, the objective was to report the experience of pharmacy and nursing students in a private chemotherapy outpatient clinic in Belém do Pará, through an extracurricular internship. The period of activities took place from August to December 2021 in the chemotherapy administration ward sector, in the chemotherapy handling center and in the scope of the outpatient's central pharmacy, under the direct supervision of the responsible preceptors. After completing the internship, it was possible to observe the role and contribution of the oncologist pharmacist in the Multiprofessional Antineoplastic Therapy Team (EMTA) and the correlation of theory with professional practice. With regard to nursing, knowledge about cancer patient care and hospital management were present throughout the period of activities. In summary, such a scenario of practice is important for academics in the health area to expand their knowledge in oncology and to train themselves for the demands of this specialty.